2017
DOI: 10.3889/oamjms.2017.065
|View full text |Cite
|
Sign up to set email alerts
|

Study of Visfatin Level in Type 1 Diabetic Children and Adolescents

Abstract: BACKGROUND:Visfatin is an intracellular enzyme, known as nicotinamide phosphoribosyltransferase (Nampt) and pre-B-cell colony-enhancing factor (PBEF-1). It has insulin-mimetic effects and lowers plasma glucose levels.AIM:The aim of the work was to assess serum concentration of Visfatin in type 1 diabetic children and adolescents and study its relationships with duration of diabetes, body mass index (BMI), glycemic control, insulin dosage, lipid profile and microvascular complications.MATERIAL AND METHODS:Fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, results concerning visfatin in T1DM and/or HD are limited and conflicting. In previous studies, circulating visfatin levels in T1DM were higher [80,81] or lower [82][83][84] compared to healthy controls. Recent studies have suggested a relationship between increased visfatin levels and chronic autoimmune thyroiditis [78,85].…”
Section: Discussionmentioning
confidence: 81%
“…However, results concerning visfatin in T1DM and/or HD are limited and conflicting. In previous studies, circulating visfatin levels in T1DM were higher [80,81] or lower [82][83][84] compared to healthy controls. Recent studies have suggested a relationship between increased visfatin levels and chronic autoimmune thyroiditis [78,85].…”
Section: Discussionmentioning
confidence: 81%
“…Rafieian-Kopaei and Nasri reported a significant difference of serum Leptin between males and females in 72 renal transplant recipients; there was no relationship between serum Leptin with body mass index, age, and creatinine clearance, however, there was a negative relationship between Leptin and the duration of renal transplantation (22). Comparing the Visfatin serum levels in renal transplant recipients with healthy volunteers, some studies, reported that Visfatin was associated with inflammatory markers and may be able to justify the relationship between inflammation and levels of Adipocytokines in longterm renal transplant recipients (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin is upregulated by hypoxia in adipocytes [45], inflammation and hyperglycemia and downregulated by insulin, somatostatin and statins. Previous studies reported that plasma levels and tissue expression of visfatin increased in parallel with diabetes [46]. Visfatin was reported to have insulin-mimetic effects [47] and lowers plasma glucose levels [48].…”
Section: Many Experimental and Clinical Reports Have Been Conductedmentioning
confidence: 98%